Laminate resin sheet for molding and molded article using the same
Patent Information
- Application Number
- JP2023107726
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
【0009】 本発明によれば、高硬度と耐擦傷性を有し、成形時に外観異常が生じにくく密着性に優れた成形用積層樹脂シートおよびそれを用いた樹脂成形品が提供される。
Smart Images

Figure 2025006744000018 
Figure 2025006744000001 
Figure 2025006744000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a moldable laminated resin sheet and a molded article using the same. [Background technology]
[0002] Resin molded articles are used for automobile interior parts such as instrument covers, housings for home appliances, office automation equipment, personal computers, and small portable devices, touch panel display surfaces for mobile phone terminals, etc. Resin molded articles used for such purposes are produced by molding a molding resin sheet.
[0003] Polycarbonate (PC) resin has been attracting attention as a resin suitable for the above-mentioned applications. PC resin is known as an engineering plastic (engineering plastics) that is excellent in transparency, light weight, and impact resistance, and is suitably applied to the above-mentioned applications.
[0004] For example, Patent Document 1 describes an invention relating to a polycarbonate resin laminate with a hard coat layer for hot bending, which is characterized in that a hard coat layer is laminated on at least one surface of a polycarbonate resin. The invention described in Patent Document 1 provides a method for producing a curved member that is excellent in abrasion resistance, hot bending property, and adhesion after hot bending.
[0005] However, as described in Patent Document 1, the pencil hardness of the outermost surface of a polycarbonate resin molded product is insufficient, and therefore the product is easily scratched by contact with hard members. This poses the problem that the product cannot be used for applications requiring high surface hardness, such as the housings of small portable devices or the touch panel display surfaces of mobile phone terminals and the like. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] WO2021 / 070632 Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a molding laminated resin sheet which has high hardness and scratch resistance, is less likely to cause appearance defects during molding, and has excellent adhesion, and to provide a molded product using the same. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the present inventors have found that the above problems can be solved by providing a high-hardness resin layer on a polycarbonate resin layer (substrate layer) and further providing a hard coat layer containing a specific component on the high-hardness resin layer. That is, the present invention is as follows. <1> a high-hardness resin layer containing a high-hardness resin; a substrate layer including a polycarbonate resin (a1) disposed on one surface side of the high-hardness resin layer; A hard coat layer disposed on the other surface side of the high-hardness resin layer, the hard coat layer has an indentation creep of 7.0% or less and a maximum indentation depth of 890 nm or less in an indentation test; The hard coat layer is (A) a 2- to 15-functional (meth)acrylate oligomer, (B) a mono- or di-functional (meth)acrylate monomer having a molecular weight of less than 200; (C) a photoinitiator, and (D) Surface Modifier A hard coating composition comprising The content of the component (C) in the moldable laminate resin sheet is 1.2 to 1.8 parts by mass per 100 parts by mass of the total of the components (A), (B), (C) and (D). <2> The indentation creep in the indentation test is 5.3 to 7.0%, and the maximum indentation depth is 700 to 890 nm. <1> 2. The molding laminate resin sheet according to claim 1 . <3> the content of the (A) component is 40 to 70 parts by mass relative to 100 parts by mass of the total of the (A), (B), (C), and (D) components, the content of the (B) component is 20 to 55 parts by mass per 100 parts by mass of the total of the (A), (B), (C), and (D) components, The content of the component (D) is 0.1 to 10 parts by mass per 100 parts by mass of the total of the components (A), (B), (C), and (D). <1> or <2> 2. The molding laminate resin sheet according to claim 1 . <4> The polycarbonate resin (a1) is an aromatic polycarbonate resin. <1> ~ <3> 1. The molding laminate resin sheet according to claim 1 , <5> The aromatic polycarbonate resin is represented by the following formula (3a): [ka] The above-mentioned structural unit represented by <1> ~ <4> 1. The molding laminate resin sheet according to claim 1 , <6> The content of the polycarbonate resin (a1) is 75 to 100% by mass based on the total mass of the base layer. <1> ~ <5> 1. The molding laminate resin sheet according to claim 1 , <7> The content of the high-hardness resin is 70 to 100% by mass based on the total mass of the high-hardness resin layer. <1> ~ <6> 1. The molding laminate resin sheet according to claim 1 , <8> The total thickness of the base layer and the high-hardness resin layer is 0.5 to 3.5 mm. <1> ~ <7> 1. The molding laminate resin sheet according to claim 1 , <9> The ratio of the thickness of the base material layer to the total thickness of the base material layer and the high-hardness resin layer is 75% to 99%. <1> ~ <8> 1. The molding laminate resin sheet according to claim 1 , <10> The pencil hardness of the surface of the hard coat layer is 2H or more. <1> ~ <9> 1. The molding laminate resin sheet according to claim 1 , <11> the above <1> ~ <10> 2. A molded article formed using the moldable laminate resin sheet according to claim 1. Effect of the Invention
[0009] According to the present invention, there are provided a molding laminate resin sheet which has high hardness and scratch resistance, is less likely to cause abnormal appearance during molding, and has excellent adhesion, and a resin molded product using the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram of an aluminum hot press mold used when hot press molding a moldable laminate resin sheet in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the present invention will be described in detail by way of examples and working examples. However, the present invention is not limited to the illustrated examples and working examples, and can be modified in any manner without departing from the scope of the present invention.
[0012] The molding laminated resin sheet of the present invention (hereinafter, also simply referred to as "resin sheet") includes a high-hardness resin layer containing a high-hardness resin, a substrate layer containing a polycarbonate resin (a1) arranged on one side of the high-hardness resin layer, and a hard coat layer arranged on the other side of the high-hardness resin layer. That is, the substrate layer, the high-hardness resin layer, and the hard coat layer are arranged in this order. An additional layer may be present between the substrate layer and the high-hardness resin layer, and between the high-hardness resin layer and the hard coat layer. Examples of the additional layer include, but are not limited to, an adhesive layer, a primer layer, and the like. The additional layer may not be present. According to one embodiment, the substrate layer, the high-hardness resin layer, and the hard coat layer are laminated to each other. That is, according to one embodiment, the molding laminated resin sheet has a high-hardness resin layer containing a high-hardness resin, a base layer containing a polycarbonate resin (a1) laminated on one surface of the high-hardness resin layer, and a hard coat layer laminated on the other surface of the high-hardness resin layer.
[0013] The high-hardness resin layer and the hard coat layer may be provided on at least one side of the substrate layer, and there is no particular restriction on the configuration of the other side.The high-hardness resin layer may be provided on both sides of the substrate layer, and in this case, a hard coat layer may be provided on one or both of the high-hardness resin layers.When the high-hardness resin layer is provided on both sides of the substrate layer, it is desirable to use the same high-hardness resin for the two high-hardness resin layers in order to obtain a stable resin sheet with little warping.
[0014] In the present invention, the indentation creep of the hard coat layer in the indentation test is 7.0% or less, preferably 5.0 to 6.9%, and more preferably 5.3 to 6.8%. This makes it possible to prevent the occurrence of appearance abnormalities such as cracks during molding while maintaining sufficient hardness. Note that the indentation creep represents the value of the relative change in the indentation depth when the indentation depth is measured with a constant test load. The maximum indentation depth of the hard coat layer is 890 nm or less, preferably 650 to 885 nm, and more preferably 700 to 880 nm. This makes it possible to prevent the occurrence of appearance abnormalities such as cracks during molding while maintaining sufficient hardness. The maximum indentation depth refers to the displacement of the fitted straight line when a test load is applied. In the present invention, the indentation creep and maximum indentation depth of the hard coat layer are values measured using a Fischer HM2000LT, specifically, values measured by the method described in the examples below.
[0015] The above-mentioned molding laminate resin sheet can be suitably used for manufacturing molded products having a curved shape that requires hardness. For example, it is possible to successfully manufacture components having a flat portion and a curved portion that is continuous with the flat portion, so that products having novel designs and functions can be provided.
[0016] When attempting to manufacture molded products having the above-mentioned shapes with conventional resin sheets, many problems occurred, such as cracks occurring during thermoforming, such as heat press molding, vacuum molding, pressure molding, and TOM molding. Therefore, in order to suppress the occurrence of cracks during thermoforming, it was necessary to devise measures such as reducing the hardness of the hard coat. However, when the hardness of the hard coat is reduced, although the thermoformability is improved, new problems occurred, such as the hard coat being easily scratched due to its softness and reduced chemical resistance.
[0017] In contrast, according to the present invention, since the occurrence of cracks is suppressed as described above, it is possible to provide a thermoformable resin sheet without reducing the hardness of the hard coat. The molding laminate resin sheet of the present invention has a hard hard coat layer on the surface, so it is less susceptible to scratches and has high chemical resistance. By utilizing such properties, the molding laminate resin sheet of the present invention can be used for components of display surfaces of personal computers and mobile phones, exterior and interior parts of automobiles, and curved housings and front panels of mobile phone terminals, personal computers, tablet PCs, car navigation systems, etc.
[0018] Each of the components of the resin sheet according to the present invention will be described below. <Base material layer> The substrate layer contains a polycarbonate resin (a1) and may further contain other resins, additives, and the like.
[0019] (Polycarbonate resin (a1)) The polycarbonate resin (a1) is not particularly limited as long as it contains a carbonate bond, i.e., an -[OR-OCO]- unit (wherein R may contain an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and may have a straight-chain structure or a branched structure), in the molecular main chain. However, an aromatic polycarbonate resin is preferable, and it is particularly preferable to use a polycarbonate resin containing a structural unit of the following formula (3a).
[0020] [ka]
[0021] Specifically, as the polycarbonate resin (a1), aromatic polycarbonate resins (for example, Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering Plastics Corporation) and the like can be used. By using such a polycarbonate resin, a resin sheet having superior impact resistance can be obtained.
[0022] In recent years, polycarbonate resins to which a monohydric phenol represented by the following general formula (3) has been added as a terminal terminator have been used for the purpose of controlling the glass transition temperature of the polycarbonate resin. In the present invention, polycarbonate resins to which such a terminal terminator has been added can also be used.
[0023] [ka]
[0024] In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms; R 6 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 20 carbon atoms which may have a substituent, or an aryl group having 6 to 12 carbon atoms; and n is an integer from 0 to 4; the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms. In this specification, the "alkyl group" and the "alkenyl group" may be linear or branched and may have a substituent.
[0025] The monohydric phenol represented by the general formula (3) is preferably represented by the following general formula (4).
[0026] [ka]
[0027] In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms.
[0028] R in general formula (3) or general formula (4) 5 It is more preferable that the number of carbon atoms in R is within a specific numerical range. 5 The upper limit of the number of carbon atoms in R is preferably 36, more preferably 22, and particularly preferably 18. 5 The lower limit of the number of carbon atoms is preferably 8, and more preferably 12.
[0029] R in general formula (3) or general formula (4) 5 When the upper limit of the carbon number is appropriate, the solubility of the monohydric phenol (end terminator) in organic solvents tends to be high, which is preferable since it increases the productivity during the production of the polycarbonate resin.
[0030] As an example, R 5If the carbon number of R is 36 or less, the productivity of polycarbonate resin production is high and the economic efficiency is good. 5 If the carbon number of the monohydric phenol is 22 or less, the monohydric phenol has excellent solubility in organic solvents, and the productivity in producing the polycarbonate resin can be significantly increased, and the economic efficiency is improved. An example of the polycarbonate resin using such a monohydric phenol is Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0031] R in general formula (3) or general formula (4) 5 When the lower limit of the carbon number is appropriate, the glass transition point of the polycarbonate resin is not too high, and suitable thermoformability is obtained, which is preferable.
[0032] For example, in general formula (4), R 5 When a monohydric phenol having an alkyl group having 16 carbon atoms is used as an end terminator, a polycarbonate resin excellent in glass transition temperature, melt fluidity, moldability, drawdown resistance, etc. can be obtained, and the monohydric phenol also has excellent solubility in a solvent during the production of the polycarbonate resin, which is particularly preferred.
[0033] Among the monohydric phenols represented by the general formula (3) or (4), it is particularly preferable to use either or both of parahydroxybenzoic acid hexadecyl ester and parahydroxybenzoic acid 2-hexyldecyl ester as the end terminator.
[0034] The weight average molecular weight of the polycarbonate resin (a1) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000, and even more preferably 20,000 to 65,000. When the weight average molecular weight of the polycarbonate resin (a1) is 15,000 or more, it is preferable because the impact resistance can be increased. On the other hand, when the weight average molecular weight is 75,000 or less, it is preferable because the base layer can be formed with a small heat source and the thermal stability can be maintained even when the molding conditions become high temperature. In this specification, the weight average molecular weight is the weight average molecular weight measured by gel permeation chromatography (GPC) and converted into standard polystyrene.
[0035] The Tg of the polycarbonate resin (a1) is preferably 90 to 190° C., more preferably 100 to 170° C., and even more preferably 110 to 150° C. The Tg of the polycarbonate resin (a1) can be controlled by appropriately adjusting the type and combination of the structural units of the polycarbonate resin (a1), the weight average molecular weight, and the like. In this specification, the glass transition point is a temperature calculated by the midpoint method using a differential scanning calorimeter, measuring 10 mg of a sample at a heating rate of 10° C. / min.
[0036] The polycarbonate resin (a1) contained in the substrate layer may be one type or two or more types.
[0037] The content of the polycarbonate resin (a1) in the substrate layer is preferably 75 to 100 mass % relative to the total mass of the substrate layer, more preferably 90 to 100 mass %, and particularly preferably 100 mass %. If the content of the polycarbonate resin is 75 mass % or more, impact resistance can be further improved, which is preferable.
[0038] (Other resins) Other resins that may be contained in the base layer are not particularly limited, but examples thereof include polyester resins. The polyester resin preferably contains terephthalic acid as the main dicarboxylic acid component, but may contain a dicarboxylic acid component other than terephthalic acid.
[0039] For example, a polyester resin (so-called "PETG") obtained by polycondensation of a glycol component containing 80 to 60 mol % of ethylene glycol as the main component and 20 to 40 mol % of 1,4-cyclohexanedimethanol (total 100 mol %) is preferred. The other resins may be used alone or in combination of two or more kinds.
[0040] When other resins are contained, the content thereof is preferably from 0 to 25 mass %, more preferably from 0 to 10 mass %, and particularly preferably 0 mass %, relative to the total mass of the base layer.
[0041] (Additives) The additives that may be contained in the base layer may be those that are commonly used in resin sheets.Specific examples include antioxidants, anti-coloring agents, antistatic agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, and reinforcing materials such as organic fillers and inorganic fillers.These additives may be used alone or in combination of two or more.
[0042] The amount of the additive is preferably from 0 to 10 mass %, more preferably from 0 to 7 mass %, and particularly preferably from 0 to 5 mass %, relative to the total mass of the base layer.
[0043] The method for mixing the additive and the resin is not particularly limited, and a method of compounding the entire amount, a method of dry blending a master batch, a method of dry blending the entire amount, or the like can be used.
[0044] (base material layer) The thickness of the substrate layer is preferably from 0.3 to 3.5 mm, more preferably from 0.3 to 3.0 mm, and further preferably from 1.0 to 3.0 mm.
[0045] <High hardness resin layer> The high-hardness resin layer includes a high-hardness resin. In addition, other resins, additives, etc. may be further included as necessary. In this specification, the high-hardness resin means a resin having a higher hardness than the polycarbonate resin serving as the base material, and a pencil hardness of HB or more, preferably HB to 3H, more preferably H to 3H, and even more preferably 2H to 3H. The pencil hardness of the high-hardness resin layer is a result of evaluation by a pencil scratch hardness test conforming to JIS K 5600-5-4:1999. Specifically, a pencil was pressed against the surface of the high-hardness resin layer at an angle of 45 degrees with a load of 750 g, with gradually increasing hardness, and the hardness of the hardest pencil that did not cause a scratch was evaluated as the pencil hardness.
[0046] [High hardness resin] The high-hardness resin is not particularly limited, but preferably contains at least one selected from the group consisting of resins (B1) to (B6).
[0047] (Resin (B1)) Resin (B1) is a copolymer containing (meth)acrylic acid ester structural unit (a) represented by general formula (1) and aliphatic vinyl structural unit (b) represented by general formula (2). In this case, the resin (B1) may further contain other structural units. In this specification, (meth)acrylic refers to methacrylic and / or acrylic.
[0048] [ka]
[0049] In the formula, R 1 is a hydrogen atom or a methyl group, and is preferably a methyl group. Also, R 2is an alkyl group having 1 to 18 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms. Specific examples include a methyl group, an ethyl group, a butyl group, a lauryl group, a stearyl group, a cyclohexyl group, and an isobornyl group. Of these, R 2 is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0050] In addition, R 2 is a methyl group or an ethyl group, the (meth)acrylic acid ester structural unit (a) represented by general formula (1) becomes a (meth)acrylic acid ester structural unit, and R 1 is a methyl group and R 2 When is a methyl group, the (meth)acrylic acid ester structural unit (a) represented by general formula (1) becomes a methyl methacrylate structural unit.
[0051] The (meth)acrylic acid ester structural unit (a) represented by general formula (1) may be contained in the resin (B1) either alone or in combination of two or more kinds.
[0052] [ka]
[0053] In the formula, R 3 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom. R 4 is a cyclohexyl group which may be substituted with a hydrocarbon group having 1 to 4 carbon atoms, and is preferably an unsubstituted cyclohexyl group.
[0054] R 3 is a hydrogen atom, and R 4 is a cyclohexyl group, the aliphatic vinyl structural unit (b) represented by general formula (2) is a vinylcyclohexane structural unit.
[0055] The aliphatic vinyl structural unit (b) represented by general formula (2) may be contained in the resin (B1) either alone or in combination of two or more kinds.
[0056] In the present specification, the "hydrocarbon group" may be linear, branched, or cyclic, and may have a substituent.
[0057] The other structural unit is not particularly limited, but may be a structural unit derived from an aromatic vinyl monomer containing an unhydrogenated aromatic double bond, which is generated in the process of producing the resin (B1) by polymerizing a (meth)acrylic acid ester monomer and an aromatic vinyl monomer and then hydrogenating the aromatic double bond derived from the aromatic vinyl monomer. A specific example of the other structural unit is a styrene structural unit. The resin (B1) may contain only one type of other structural unit, or two or more types of other structural units.
[0058] The total content of the (meth)acrylic acid ester structural units (a) and the aliphatic vinyl structural units (b) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and particularly preferably 98 to 100 mol %, based on all structural units of the resin (B1).
[0059] The content of the (meth)acrylic acid ester structural unit (a) represented by the general formula (1) is preferably 65 to 80 mol %, more preferably 70 to 80 mol %, based on the total structural units of the resin (B1). If the ratio of the (meth)acrylic acid ester structural unit (a) is 65 mol % or more, it is preferable because a resin layer having excellent adhesion to the base layer and excellent surface hardness can be obtained. On the other hand, if the ratio of the (meth)acrylic acid ester structural unit (a) is 80 mol % or less, it is preferable because warping due to water absorption of the resin sheet is unlikely to occur.
[0060] The content of the aliphatic vinyl structural unit (b) represented by the general formula (2) is preferably 20 to 35 mol %, more preferably 20 to 30 mol %, based on the total structural units of the resin (B1). If the content of the aliphatic vinyl structural unit (b) is 20 mol % or more, warping under high temperature and high humidity conditions can be prevented, which is preferable. On the other hand, if the content of the aliphatic vinyl structural unit (b) is 35 mol % or less, peeling at the interface with the base layer can be prevented, which is preferable.
[0061] Furthermore, the content of other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on all structural units of the resin (B1).
[0062] In this specification, the "copolymer" may have any of a random copolymer, a block copolymer, and an alternating copolymer structure.
[0063] The weight average molecular weight of the resin (B1) is not particularly limited, but from the viewpoints of strength and moldability, it is preferably from 50,000 to 400,000, and more preferably from 70,000 to 300,000.
[0064] The glass transition point of the resin (B1) is preferably 110 to 140° C., more preferably 110 to 135° C., and particularly preferably 110 to 130° C. If the glass transition point is 110° C. or higher, the resin sheet is less likely to deform or crack in a hot or humid environment, which is preferable. On the other hand, if the glass transition point is 140° C. or lower, the resin sheet is excellent in processability when molded by continuous thermal shaping using a mirror roll or a shaping roll, or by batch-type thermal shaping using a mirror mold or a shaping mold, which is preferable.
[0065] Specific examples of the resin (B1) include Optimus 7500 and 6000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) The above-mentioned resin (B1) may be used alone or in combination of two or more kinds.
[0066] When resin (B1) is used as the high hardness resin, it is preferable to use Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Company) as the polycarbonate resin (a1).
[0067] In addition, as the high hardness resin, a structural unit represented by the general formula (1) (R 1 , R 2 methyl methacrylate) at 75 mol %, and 3 is a hydrogen atom, R 4 The resin (B1) is a copolymer containing 25 mol % of cyclohexyl groups (vinylcyclohexane), the polycarbonate resin (a1) is a polycarbonate resin containing a structural unit of the formula (3a), and the monohydric phenol (R 5 It is particularly preferable to use an alkyl group having a carbon number of 8 to 22.
[0068] The method for producing the resin (B1) is not particularly limited, but a resin obtained by polymerizing at least one type of (meth)acrylic acid ester monomer and at least one type of aromatic vinyl monomer, and then hydrogenating the aromatic double bond derived from the aromatic vinyl monomer, is suitable.
[0069] The aromatic vinyl monomer is not particularly limited, but may be styrene, α-methylstyrene, p-hydroxystyrene, alkoxystyrene, chlorostyrene, and derivatives thereof, etc. Among these, the aromatic vinyl monomer is preferably styrene.
[0070] For the polymerization of the (meth)acrylic acid ester monomer and the aromatic vinyl monomer, a known method can be used, for example, a bulk polymerization method or a solution polymerization method can be used for production. The bulk polymerization method is carried out by continuously supplying a monomer composition containing the above-mentioned monomers and a polymerization initiator to a complete mixing tank and continuously polymerizing the monomers at 100 to 180° C. The above-mentioned monomer composition may contain a chain transfer agent as necessary.
[0071] The polymerization initiator is not particularly limited, but examples thereof include organic peroxides such as t-amylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, benzoyl peroxide, 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, t-hexylpropoxyisopropyl monocarbonate, t-amylperoxy normal octoate, t-butylperoxyisopropyl monocarbonate, and di-t-butyl peroxide, and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile). These can be used alone or in combination of two or more.
[0072] The chain transfer agent is not particularly limited, but examples thereof include α-methylstyrene dimer.
[0073] Examples of solvents used in the solution polymerization method include hydrocarbon solvents such as toluene, xylene, cyclohexane, and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol. These solvents may be used alone or in combination of two or more.
[0074] The solvent used in the hydrogenation reaction for hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer after polymerization of the (meth)acrylic acid ester monomer and the aromatic vinyl monomer may be the same as or different from the above-mentioned polymerization solvent. For example, hydrocarbon solvents such as cyclohexane and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol can be mentioned.
[0075] The hydrogenation method is not particularly limited, and known methods can be used. For example, the hydrogenation can be carried out in a batch or continuous flow manner at a hydrogen pressure of 3 to 30 MPa and a reaction temperature of 60 to 250°C. A reaction temperature of 60°C or higher is preferable because the reaction time is not too long. On the other hand, a reaction temperature of 250°C or lower is preferable because side reactions such as scission of molecular chains and hydrogenation of ester moieties do not occur or occur very little.
[0076] Examples of catalysts used in the hydrogenation reaction include solid catalysts in which metals such as nickel, palladium, platinum, cobalt, ruthenium, and rhodium, or oxides, salts, or complex compounds of these metals are supported on porous supports such as carbon, alumina, silica, silica-alumina, and diatomaceous earth.
[0077] It is preferable that 70% or more of the aromatic double bonds derived from the aromatic vinyl monomer are hydrogenated by the hydrogenation reaction. That is, the unhydrogenated ratio of the aromatic double bonds contained in the structural unit derived from the aromatic vinyl monomer is preferably less than 30%, more preferably less than 10%, and even more preferably less than 5%. If the unhydrogenated ratio is less than 30%, it is preferable because a resin with excellent transparency can be obtained. The structural unit of the unhydrogenated portion can be another structural unit in the resin (B1).
[0078] (Resin (B2)) Resin (B2) is a copolymer containing 6 to 77% by mass of (meth)acrylic acid ester structural units, 15 to 71% by mass of styrene structural units, and 8 to 23% by mass of unsaturated dicarboxylic acid structural units, which may further contain other structural units.
[0079] The (meth)acrylic acid ester monomer constituting the (meth)acrylic acid ester structural unit in the resin (B2) is not particularly limited, but may be acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc. Among these, the (meth)acrylic acid ester monomer is preferably methyl methacrylate. The above-mentioned (meth)acrylic acid ester monomer may be contained alone as the (meth)acrylic acid ester structural unit, or may be contained in combination of two or more kinds.
[0080] The content of the (meth)acrylic acid ester structural unit is from 6 to 77% by mass, and preferably from 20 to 70% by mass, based on the total mass of the resin (B2).
[0081] The styrene structural unit in the resin (B2) is not particularly limited, and any known styrene monomer can be used. From the viewpoint of availability, the styrene monomer may be styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, etc. Among these, from the viewpoint of compatibility, the styrene monomer is preferably styrene. The above-mentioned styrene monomer may be contained alone as the styrene structural unit, or may be contained in combination of two or more kinds.
[0082] The content of the styrene structural unit is from 15 to 71 mass %, and preferably from 20 to 66 mass %, based on the total mass of the resin (B2).
[0083] The unsaturated dicarboxylic anhydride monomer constituting the unsaturated dicarboxylic acid constituent unit in the resin (B2) is not particularly limited, and examples thereof include acid anhydrides such as maleic acid, itaconic acid, citraconic acid, and aconitic acid. Among these, from the viewpoint of compatibility with styrene-based monomers, the unsaturated dicarboxylic anhydride monomer is preferably maleic anhydride. The above-mentioned unsaturated dicarboxylic anhydride monomer may be contained alone as the unsaturated dicarboxylic acid constituent unit, or may be contained in combination of two or more kinds.
[0084] The content of the unsaturated dicarboxylic acid constituent units is from 8 to 23 mass %, and preferably from 10 to 23 mass %, based on the total mass of the resin (B2).
[0085] Examples of other structural units in the resin (B2) include N-phenylmaleimide.
[0086] The content of other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on all structural units of the resin (B2).
[0087] The total content of the above-mentioned (meth)acrylic acid ester structural units, styrene structural units, and unsaturated dicarboxylic acid structural units is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and particularly preferably 98 to 100 mol %, based on all structural units of the resin (B2).
[0088] The weight average molecular weight of the resin (B2) is not particularly limited, but is preferably from 50,000 to 300,000, and more preferably from 80,000 to 200,000.
[0089] The glass transition point of the resin (B2) is preferably from 90 to 150°C, more preferably from 100 to 150°C, and particularly preferably from 115 to 150°C.
[0090] Specific examples of the resin (B2) include Resisfy R100, R200, and R310 (manufactured by Denka), Delpet 980N (manufactured by Asahi Kasei), and hw55 (manufactured by Daicel-Evonik), etc. The above-mentioned resin (B2) may be used alone or in combination of two or more kinds.
[0091] When resin (B2) is used as the high hardness resin, it is preferable to use a polycarbonate resin containing a structural unit of formula (3a) as polycarbonate resin (a1). Furthermore, a monohydric phenol (R 5 It is particularly preferable to use a polycarbonate resin having a carbon number of 8 to 22. Examples of such polycarbonate resins include Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and Iupilon E-2000 (manufactured by Mitsubishi Engineering Plastics Corporation).
[0092] Furthermore, when using a copolymer (R100 or R200; manufactured by Denka) resin (B2) composed of 6 to 26 mass% methyl methacrylate structural units, 55 to 21 mass% styrene structural units, and 15 to 23 mass% maleic anhydride structural units as the high-hardness resin, a preferred embodiment is one in which Iupizeta T-1380 is used as the polycarbonate resin (a1).
[0093] Furthermore, when using resin (B2) which is a copolymer (R310; manufactured by Denka) composed of 6 mass% methyl methacrylate structural units, 71 mass% styrene structural units, and 23 mass% maleic anhydride structural units as a high-hardness resin, it is particularly preferable to use Iupizeta T-1380 as polycarbonate resin (a1).
[0094] The method for producing the resin (B2) is not particularly limited, but examples thereof include bulk polymerization and solution polymerization.
[0095] (Resin (B3)) Resin (B3) is a polymer containing a structural unit (c) represented by formula (5). In this case, the polymer preferably further contains a structural unit (d) represented by formula (6). The polymer may further contain other structural units.
[0096] [ka]
[0097] The content of the structural unit (c) represented by formula (5) is preferably 50 to 100 mol %, more preferably 60 to 100 mol %, and particularly preferably 70 to 100 mol %, based on all structural units of the resin (B3).
[0098] [ka]
[0099] The content of the structural unit (d) represented by formula (6) is preferably 0 to 50 mol %, more preferably 0 to 40 mol %, and particularly preferably 0 to 30 mol %, based on all structural units of the resin (B3).
[0100] The content of other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on all structural units of the resin (B3).
[0101] The total content of the structural units (c) and (d) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 98 to 100 mol %, based on all structural units in the resin (B3).
[0102] The weight average molecular weight of the resin (B3) is preferably from 15,000 to 75,000, more preferably from 20,000 to 70,000, and particularly preferably from 25,000 to 65,000.
[0103] The glass transition point of the resin (B3) is preferably from 105 to 150°C, more preferably from 110 to 140°C, and particularly preferably from 110 to 135°C.
[0104] Specific examples of the resin (B3) include Iupilon KH3410UR, KH3520UR, and KS3410UR (manufactured by Mitsubishi Engineering Plastics Corporation), etc. The above-mentioned resin (B3) may be used alone or in combination of two or more kinds.
[0105] When resin (B3) is used as the high hardness resin, it is preferable to use a polycarbonate resin containing a structural unit of formula (3a) as polycarbonate resin (a1). Furthermore, a monohydric phenol (R 5 A particularly preferred embodiment is one in which a polycarbonate resin having a carbon number of 8 to 22 is used. An example of such a polycarbonate resin is Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Company). In particular, it is preferred to use Iupilon KS3410UR (manufactured by Mitsubishi Engineering Plastics Corporation) as the resin (B3) and Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Company) as the polycarbonate resin (a1).
[0106] In addition, when resin (B3) is used as the high hardness resin, it is preferable to contain other resins than resins (B1) to (B6). In this case, the other resins than resins (B1) to (B6) are preferably resins that do not contain structural unit (c) but contain structural unit (d), and more preferably resins that consist only of structural unit (d). Specifically, aromatic polycarbonate resins (e.g., Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering Plastics Corporation) and the like can be used.
[0107] When resins other than the resins (B1) to (B6) are contained, the resin (B3) is contained in an amount of preferably 45 mass % or more, and more preferably 55 mass % or more, based on the total resins contained in the high-hardness resin layer.
[0108] The method for producing the resin (B3) is not particularly limited, but it can be produced by the same method as the method for producing the polycarbonate resin (a1) described above, except that bisphenol C is used as the monomer.
[0109] (Resin (B4)) Resin (B4) is a copolymer containing 5 to 20 mass% of styrene structural units, 60 to 90 mass% of (meth)acrylic acid ester structural units, and 5 to 20 mass% of N-substituted maleimide structural units. The resin (B4) may further contain other structural units.
[0110] The styrene structural unit in the resin (B4) is not particularly limited, and any known styrene monomer can be used. From the viewpoint of availability, the styrene monomer may be styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, etc. Among these, from the viewpoint of compatibility, the styrene monomer is preferably styrene. The above-mentioned styrene monomer may be contained alone as the styrene structural unit, or may be contained in combination of two or more kinds.
[0111] The content of the styrene structural unit is from 5 to 20 mass %, preferably from 5 to 15 mass %, and more preferably from 5 to 10 mass %, based on the total mass of the resin (B4).
[0112] The (meth)acrylic acid ester monomer constituting the (meth)acrylic acid ester structural unit in the resin (B4) is not particularly limited, but may be acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc. Among these, the (meth)acrylic acid ester monomer is preferably methyl methacrylate. The above-mentioned (meth)acrylic acid ester monomer may be contained alone as the (meth)acrylic acid ester structural unit, or may be contained in combination of two or more kinds.
[0113] The content of the (meth)acrylic acid ester structural unit is from 60 to 90 mass %, preferably from 70 to 90 mass %, and more preferably from 80 to 90 mass %, based on the total mass of the resin (B4).
[0114] Examples of the N-substituted maleimide structural unit in the resin (B4) include structural units derived from N-arylmaleimides such as N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-nitrophenylmaleimide, and N-tribromophenylmaleimide. Among these, structural units derived from N-phenylmaleimide are preferred from the viewpoint of compatibility with acrylic resins. The structural units derived from the above-mentioned N-substituted maleimide may be contained alone as the N-substituted maleimide structural unit, or may be contained in combination of two or more kinds.
[0115] The content of the N-substituted maleimide constituent units is from 5 to 20 mass %, preferably from 5 to 15 mass %, and more preferably from 5 to 10 mass %, relative to the total mass of the resin (B4).
[0116] Examples of the other structural units include a (meth)acrylic acid ester structural unit represented by general formula (1) and an aliphatic vinyl structural unit represented by general formula (2), etc. In this case, the general formula (1) and the general formula (2) are the same as those of the above-mentioned resin (B1).
[0117] The content of other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, and particularly preferably 2 mol % or less, based on all structural units of the resin (B4).
[0118] The total content of the styrene structural units, the (meth)acrylic acid ester structural units, and the N-substituted maleimide structural units is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 98 to 100 mol %, based on all structural units of the resin (B4).
[0119] The weight average molecular weight of the resin (B4) is preferably from 50,000 to 250,000, and more preferably from 100,000 to 200,000.
[0120] The glass transition point of the resin (B4) is preferably from 110 to 150°C, more preferably from 120 to 150°C, and particularly preferably from 130 to 150°C.
[0121] A specific example of the resin (B4) is Delpet PM120N (manufactured by Asahi Kasei Corporation). It is also preferable to use Polyimilex PML203 (manufactured by Nippon Shokubai) which is composed of 9% by mass of styrene structural units, 78% by mass of (meth)acrylic acid ester structural units, and 13% by mass of N-substituted maleimide structural units, as the resin (B4). The above-mentioned resins (B4) may be used alone or in combination of two or more kinds.
[0122] When resin (B4) is used as the high hardness resin, it is preferable to use a polycarbonate resin containing a structural unit of formula (3a) as polycarbonate resin (a1). Furthermore, a monohydric phenol (R 5 A particularly preferred embodiment is one in which a polycarbonate resin having a carbon number of 8 to 22 is used. An example of such a polycarbonate resin is Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Co., Ltd.). In particular, it is preferred to use Delpet PM-120N, which is composed of 7% by mass of styrene structural units, 86% by mass of (meth)acrylic acid ester structural units, and 7% by mass of N-substituted maleimide structural units, as the resin (B4), and Iupizeta T-1380 as the polycarbonate resin (a1).
[0123] The method for producing the resin (B4) is not particularly limited, but it can be produced by solution polymerization, bulk polymerization, or the like.
[0124] (Resin (B5)) Resin (B5) is a polymer containing a structural unit (e) represented by formula (7). In this case, resin (B5) may further contain other structural units.
[0125] [ka]
[0126] The content of the structural unit (e) represented by formula (7) relative to all structural units of the resin (B5) is preferably 80 to 100 mol %, more preferably 90 to 100 mol %, and particularly preferably 95 to 100 mol %.
[0127] Examples of the other structural units include a structural unit represented by formula (5) and a structural unit represented by formula (6), in which formula (5) and formula (6) are the same as those in the resin (B3) described above.
[0128] The content of other structural units is preferably 20 mol % or less, more preferably 10 mol % or less, and particularly preferably 5 mol % or less, based on all structural units of the resin (B5).
[0129] The weight average molecular weight of the resin (B5) is preferably from 10,000 to 1,000,000, and more preferably from 15,000 to 50,000.
[0130] The glass transition point of the resin (B5) is preferably from 120 to 200°C, more preferably from 130 to 190°C, and particularly preferably from 140 to 190°C.
[0131] A specific example of the resin (B5) is Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical Co., Inc.) The above-mentioned resin (B5) may be used alone or in combination of two or more kinds.
[0132] When resin (B5) is used as the high hardness resin, it is preferable to use a polycarbonate resin containing the structural unit of formula (3a) as polycarbonate resin (a1). An example of such a polycarbonate resin is Iupilon E-2000 (manufactured by Mitsubishi Engineering Plastics). In particular, it is preferable to use Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical) as resin (B5) and Iupilon E-2000 (manufactured by Mitsubishi Engineering Plastics) as polycarbonate resin (a1).
[0133] When resin (B5) is used as the high hardness resin, it is preferable to include other resins than resins (B1) to (B6). In this case, the other resins than resins (B1) to (B6) are preferably resins that do not include structural unit (c) but include structural unit (d), and more preferably resins that consist of structural unit (d). Specifically, aromatic polycarbonate resins (e.g., Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering Plastics Corporation) and the like can be used.
[0134] When resins other than the resins (B1) to (B6) are contained, the resin (B5) is contained in an amount of preferably 45 mass % or more, and more preferably 55 mass % or more, based on the total resins contained in the high-hardness resin layer.
[0135] The method for producing resin (B5) is not particularly limited, but it can be produced by the same method as the method for producing polycarbonate resin (a1) described above, except that bisphenol AP is used as the monomer.
[0136] (Resin (B6)) The resin (B6) is a copolymer containing 50 to 95% by mass of styrene structural units and 5 to 50% by mass of unsaturated dicarboxylic acid structural units.
[0137] As the styrene structural unit, the styrene monomers described in the resin (B4) can be used. The resin (B6) may use these styrene structural units alone or in combination of two or more kinds.
[0138] The content of the styrene structural unit is preferably from 50 to 95 mass %, more preferably from 60 to 90 mass %, and even more preferably from 65 to 87 mass %, based on the total mass of the resin (B6).
[0139] Examples of the unsaturated dicarboxylic acid anhydride monomer constituting the unsaturated dicarboxylic acid structural unit include acid anhydrides such as maleic acid, itaconic acid, citraconic acid, and aconitic acid. Among these, maleic anhydride is preferred from the viewpoint of compatibility with styrene-based monomers. The above-mentioned unsaturated dicarboxylic acid anhydride monomers may be used alone or in combination of two or more.
[0140] The content of the unsaturated dicarboxylic acid constituent units is preferably from 5 to 50 mass %, more preferably from 10 to 40 mass %, and even more preferably from 13 to 35 mass %, based on the total mass of the resin (B6).
[0141] Resin (B6) may contain other structural units in addition to the above-mentioned structural units. Examples of the other structural units include a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2).
[0142] [ka] In the formula, R 1 and R 2 is the same as above.
[0143] [ka] In the formula, R 3 and R 4is the same as above.
[0144] The content of the other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 2 mol % or less, based on all structural units of the resin (B6).
[0145] The weight average molecular weight of the resin (B6) is preferably from 50,000 to 250,000, and more preferably from 50,000 to 100,000.
[0146] The glass transition point of the resin (B6) is preferably from 110 to 150°C, more preferably from 120 to 150°C, and particularly preferably from 130 to 150°C.
[0147] Specific examples of the resin (B6) include XIBOND140 and XIBOND160 (manufactured by Polyscope Co., Ltd.) The above-mentioned resin (B6) may be used alone or in combination of two or more kinds.
[0148] When resin (B6) is used as the high hardness resin, it is preferable to use a polycarbonate resin containing a structural unit of formula (3a) as polycarbonate resin (a1). Furthermore, a monohydric phenol (R 5 A particularly preferred embodiment is one in which a polycarbonate resin having a carbon number of 8 to 22 is used. An example of such a polycarbonate resin is Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Co., Ltd.). In particular, it is preferred to use an alloy of XIBOND160, which is composed of 78% by mass of styrene structural units and 22% by mass of maleic anhydride structural units, and an acrylic resin as the resin (B6), and to use Iupizeta T-1380 as the polycarbonate resin (a1).
[0149] The method for producing the resin (B6) is not particularly limited, but it can be produced by solution polymerization, bulk polymerization, or the like.
[0150] At least one selected from the group consisting of the above-mentioned resins (B1) to (B6) may be contained as an alloy.
[0151] The alloy is not particularly limited, but examples thereof include an alloy of two types of resins (B1), an alloy of two types of resins (B2), an alloy of two types of resins (B3), an alloy of two types of resins (B4), an alloy of two types of resins (B5), an alloy of two types of resins (B6), an alloy of resin (B1) and resin (B2), an alloy of resin (B2) and resin (B4), an alloy of resin (B2) and another high-hardness resin, an alloy of resin (B2) and acrylic resin, and an alloy of resin (B6) and acrylic resin.
[0152] Examples of the other high hardness resins include methyl methacrylate-styrene copolymers and acrylonitrile-butadiene-styrene copolymers.
[0153] Examples of the acrylic resin include polymethyl methacrylate, copolymers of methyl methacrylate and methyl acrylate or ethyl acrylate, etc. Commercially available products include ACRYPET (manufactured by Mitsubishi Chemical Corporation), SUMIPEXX (manufactured by Sumitomo Chemical Co., Ltd.), PARAPET (manufactured by Kuraray Co., Ltd.), etc.
[0154] When two types of resins are alloyed, it is preferable to use an alloy of resins having a higher glass transition temperature. The above alloys may be used alone or in combination of two or more kinds.
[0155] The alloy may be produced by, but is not limited to, a method in which the alloy is melt-kneaded at a cylinder temperature of 240° C. using a twin-screw extruder with a screw diameter of 26 mm, extruded in the form of strands, and pelletized with a pelletizer.
[0156] The high-hardness resin layer may contain one type or two or more types of high-hardness resins. When two or more types are selected from the resins (B1) to (B6), they may be selected from the same or different categories, and may further contain high-hardness resins other than the resins (B1) to (B6).
[0157] The content of the high-hardness resin in the high-hardness resin layer is preferably 70 to 100 mass %, more preferably 80 to 100 mass %, and particularly preferably 100 mass %, based on the total mass of the high-hardness resin layer.
[0158] [Other resins] The high-hardness resin layer may contain other resins besides the high-hardness resin. Examples of the other resins include methyl methacrylate-styrene copolymers, polymethyl methacrylate, polystyrene, polycarbonate, cycloolefin (co)polymer resins, acrylonitrile-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, various elastomers, etc. These other resins may be used alone or in combination of two or more.
[0159] The content of the other resin is preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 0% by mass, based on the total mass of the high-hardness resin layer.
[0160] [Additives] The high-hardness resin layer may contain additives, etc. As the additives, the above-mentioned ones can be used.
[0161] [High hardness resin layer] The thickness of the high-hardness resin layer is preferably 10 to 250 μm, more preferably 30 to 200 μm, and particularly preferably 60 to 150 μm. When the thickness of the high-hardness resin layer is 10 μm or more, the surface hardness is increased, which is preferable. On the other hand, when the thickness of the high-hardness resin layer is 250 μm or less, the impact resistance is increased, which is preferable.
[0162] [Lamination of high-hardness resin layer onto base layer] As described above, an additional layer may exist between the substrate layer and the high-hardness resin layer, but here, a case where a high-hardness resin layer is laminated on the substrate layer will be described.
[0163] The method of laminating the high-hardness resin layer on the substrate layer is not particularly limited, and examples thereof include a method of overlapping a substrate layer and a high-hardness resin layer formed separately and heating and pressing them together; a method of overlapping a substrate layer and a high-hardness resin layer formed separately and bonding them together with an adhesive; a method of co-extrusion molding the substrate layer and the high-hardness resin layer; a method of in-mold molding the substrate layer into a previously formed high-hardness resin layer to integrate them, etc. Among these, the co-extrusion molding method is preferred from the viewpoints of production cost and productivity.
[0164] The method of co-extrusion is not particularly limited. For example, in the feed block method, a high-hardness resin layer is arranged on one side of a base layer in a feed block, extruded into a sheet shape with a T-die, and then cooled while passing through a forming roll to form a desired laminate. In the multi-manifold method, a high-hardness resin layer is arranged on one side of a base layer in a multi-manifold die, extruded into a sheet shape, and then cooled while passing through a forming roll to form a desired laminate. The above method can be used in the same manner when laminating a high-hardness resin layer onto a layer other than the substrate layer.
[0165] The total thickness of the base layer and the high-hardness resin layer is preferably 0.5 to 3.5 mm, more preferably 0.5 to 3.0 mm, and even more preferably 1.2 to 3.0 mm. If the total thickness is 0.5 mm or more, the rigidity of the sheet can be maintained, which is preferable. On the other hand, if the total thickness is 3.5 mm or less, it is preferable to prevent the sensitivity of the touch sensor from being deteriorated when a touch panel is installed under the sheet.
[0166] The ratio of the thickness of the base layer to the total thickness of the base layer and the high-hardness resin layer is preferably 75% to 99%, more preferably 80% to 99%, and particularly preferably 85% to 99%. By setting it in the above range, both hardness and impact resistance can be achieved.
[0167] <Hard coat layer> In this specification, the term "hard coat" refers to a coating film formed by polymerizing a hard coating composition containing a monomer, oligomer, or prepolymer containing a (meth)acryloyl group as a polymerizable group to form a crosslinked structure.
[0168] In the present invention, the hard coating composition contains (A) a di- to 15-functional (meth)acrylate oligomer, (B) a mono- or di-functional (meth)acrylate monomer having a molecular weight of less than 200, (C) a photopolymerization initiator, and (D) a surface modifier. In this specification, the photopolymerization initiator refers to a photoradical generator.
[0169] The content of the (meth)acrylate oligomer as component (A) is preferably 40 to 70 parts by mass, more preferably 48 to 67 parts by mass, and particularly preferably 56 to 63 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D).
[0170] The content of the (meth)acrylate monomer as component (B) is preferably 20 to 55 parts by mass, more preferably 28 to 50 parts by mass, and particularly preferably 36 to 45 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D).
[0171] The content of the photopolymerization initiator, component (C), is 1.2 to 1.8 parts by mass, preferably 1.25 to 1.7 parts by mass, and more preferably 1.3 to 1.6 parts by mass, relative to 100 parts by mass of the total of components (A), (B), (C), and (D). If the content of component (C) is less than 1.2 parts by mass, it may cause insufficient curing of the hard coat, and if it exceeds 1.8 parts by mass, it may cause cracks to occur on the surface of the hard coat during molding.
[0172] The content of the surface modifier, which is component (D), is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D).
[0173] The viscosity of the hard coating composition containing the components (A) to (D) at 25°C is preferably 400 cps or less, more preferably 300 cps or less, and most preferably 150 cps or less. The lower limit is usually about 10 cps. If the viscosity of the hard coating composition at 25°C exceeds 400 cps, the coating film becomes thick during application, cracks are likely to occur after thermoforming, and the processability during cutting may be significantly reduced. If the viscosity of the hard coating composition at 25°C is less than 10 cps, the film thickness becomes thin during hard coat production, which may lead to a decrease in pencil hardness. The viscosity of the hard coating composition can be measured under conditions of 25°C using a vibration type viscometer VM-100A-L manufactured by Sekonic.
[0174] <Component (A)> [(Meth)acrylate oligomer] The (meth)acrylate oligomer, which is the component (A) used in the present invention, is a polyfunctional (meth)acrylate oligomer having 2 to 15 functionalities, preferably 2 to 9 functionalities, and more preferably 2 to 6 functionalities. The oligomer referred to here is a polymer having preferably 2 or more constitutional units, more preferably about 2 to 20 constitutional units, and the lower limit of the molecular weight is about 400 or more, more preferably 1200 or more. The upper limit of the molecular weight of the oligomer is preferably 6000 or less, more preferably 4000 or less.
[0175] Specific examples of the component (A) include the polyfunctional (meth)acrylate oligomers (1) to (4) shown below. (1) Multifunctional polyol (meth)acrylate oligomers, i.e., polyacrylate or polymethacrylate oligomers obtained by reacting a polyhydric alcohol (polyol or polyhydroxy-containing compound) with a compound selected from the group consisting of acrylic acid, methacrylic acid and their derivatives. (2) Polyfunctional polyester (meth)acrylate oligomers, that is, oligomers of polyacrylates or polymethacrylates of saturated or unsaturated polyesters obtained from polyhydric alcohols (polyols), polycarboxylic acids (polybasic acids or polybasic carboxylic acids) or their anhydrides, and acrylic acid, methacrylic acid, or derivatives thereof. (3) Multifunctional urethane (meth)acrylate oligomers, i.e., urethane polyacrylate or urethane polymethacrylate oligomers obtained from polyisocyanates and compounds having active hydrogen and acryloyloxy groups or methacryloyloxy groups. (4) Multifunctional polyglycidyl ether (meth)acrylate oligomers, i.e., polyacrylate or polymethacrylate oligomers obtained from polyglycidyl ether and acrylic acid, methacrylic acid or derivatives thereof.
[0176] Examples of the polyhydric alcohol (polyol) used in the production of the above (1) polyfunctional polyol (meth)acrylate oligomer include dihydric alcohols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols having a number average molecular weight of 300 to 1000, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, 2,2'-thiodiethanol, and 1,4-cyclohexanedimethanol; trihydric alcohols such as trimethylolethane, trimethylolpropane, pentaglycerol, glycerol, 1,2,4-butanetriol, and 1,2,6-hexanetriol; and tetrahydric or higher alcohols such as pentaerythritol, diglycerol, and dipentaerythritol.
[0177] The above (2) polyfunctional polyester (meth)acrylate oligomer is obtained by the reaction of (meth)acrylic acid, a polybasic carboxylic acid (anhydride), and a polyol (a polyhydroxy-containing compound or a polyhydric alcohol). More specifically, a polyester polyol is produced by a dehydration condensation reaction of a dibasic carboxylic acid (anhydride) and a polyol, and then the reaction product is reacted with acrylic acid or methacrylic acid to obtain a polyfunctional polyester (meth)acrylate oligomer.
[0178] The polyhydroxy-containing compounds, also called "polyols", used in the preparation of polyester polyols are preferably compounds having three or more hydroxy groups. In general, the polyols that can be used in the present invention are compounds having 3 to 6 hydroxy groups, preferably 3 to 4 hydroxy groups, and 2 to about 36 carbon atoms. Such polyols include branched or straight chain aliphatic polyols, alicyclic polyols, aromatic polyols, and polyether polyols. Aliphatic polyols can include triols, such as glycerin, trimethylolpropane, and trimethylolethane; tetraols, such as pentaerythritol and di-trimethylolpropane; and hexaols, such as dipentaerythritol. Additionally, aliphatic and cycloaliphatic polyols can be reacted with various amounts of ethylene oxide and / or propylene oxide to obtain ethoxylated and / or propoxylated polyols. Examples of ethoxylated and / or propoxylated polyols include ethoxylated trimethylolpropane, propoxylated trimethylolpropane, ethoxylated glycerin, propoxylated glycerin, ethoxylated pentaerythritol, and propoxylated pentaerythritol.
[0179] An example of the aromatic polyol is bisphenol A diacrylate. The polyether polyols that can be used in the present invention are both aromatic polyethers and aliphatic polyethers.The aliphatic groups of the polyether polyols can be linear, branched, or cyclic.Examples of polyether polyols include tri-glycols, such as triethylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, and mixed polyethers, such as poly(propylene-ethylene) glycol.
[0180] Examples of dibasic carboxylic acids (anhydrides) used in the production of polyester polyols include aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, and sebacic acid; alicyclic dicarboxylic acids such as tetrahydrophthalic acid and 3,6-endomethylenetetrahydrophthalic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; trimellitic acid; pyromellitic acid; thiodiglycolic acid; thiodivaleric acid; diglycolic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid. Chlorides, anhydrides, or esters of these can also be used. Anhydrides of these dibasic carboxylic acids are preferably used. Particularly preferred are alicyclic dicarboxylic acid anhydrides such as tetrahydrophthalic anhydride. Polyester polyols are polyols having ester bonds. For example, excess polyols are reacted with dibasic acids (anhydrides) to obtain low molecular weight compounds having about 1 to about 6 ester bonds and reactive hydroxyl groups. The above polyols can be used alone or in mixtures to produce polyester polyols. The polyester polyols may also be further reacted with various amounts of ethylene oxide and / or propylene oxide to provide ethoxylated and / or propoxylated polyester polyols.
[0181] The (2) polyfunctional polyester (meth)acrylate oligomer used in the present invention can be obtained by reacting the polyester polyol thus obtained with a compound selected from the group consisting of acrylic acid, methacrylic acid, and derivatives thereof. Of the compounds selected from the group consisting of acrylic acid, methacrylic acid and derivatives thereof, it is more preferable to use acrylic acid.
[0182] In the above (2) multifunctional polyester (meth)acrylate oligomer, the polyol (polyhydroxy-containing compound) can be used alone or in combination with other polyhydroxy-containing compounds. Furthermore, the compounds selected from the group consisting of acrylic acid, methacrylic acid and their derivatives can be used alone or in combination with each other. When a mixture of polyhydroxy-containing compounds is used, a mixed ester product is obtained. Similarly, when a mixture of acrylic acid and methacrylic acid is used, the product is a mixed acrylate oligomer.
[0183] A preferred polyester (meth)acrylate oligomer is a di- to tetra-functional acrylate oligomer obtained by subjecting tetrahydrophthalic anhydride, trimethylolpropane, and acrylic acid to an esterification reaction by a conventional method.
[0184] Examples of the (3) polyfunctional urethane (meth)acrylate oligomer include a urethane reaction product between a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule and a polyisocyanate, and a urethane reaction product between an isocyanate compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule.
[0185] In the production of a polyfunctional urethane (meth)acrylate oligomer, examples of the polyisocyanate used in the urethanization reaction include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates (for example, diisocyanates such as hydrogenated tolylene diisocyanate and hydrogenated xylylene diisocyanate), di- or triisocyanates such as triphenylmethane triisocyanate and dimethylene triphenyl triisocyanate, and polyisocyanates obtained by cyanurating a diisocyanate.
[0186] In the production of a polyfunctional urethane (meth)acrylate oligomer, examples of polyols used in the production of an isocyanate compound include the compounds exemplified as the polyhydric alcohols used in the production of the above (1) polyfunctional polyol (meth)acrylate oligomer. Specific examples of isocyanate compounds obtained by reacting the above polyols with polyisocyanates include trimethylolpropane toluylene diisocyanate. The "compound containing active hydrogen and an acryloyloxy group (or a methacryloyloxy group)" used in the production of the polyfunctional urethane (meth)acrylate oligomer is a compound containing a hydroxyl group and an acryloyloxy group (or a methacryloyloxy group). Specific examples include 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate.
[0187] Specific examples of polyfunctional urethane (meth)acrylate oligomers that are particularly preferably used in the present invention include trimethylolpropane toluylene diisocyanate, or a reaction product of an isocyanurate group-containing polyisocyanate with a compound containing active hydrogen and a (meth)acryloyloxy group. More specifically, examples of the oligomer include a triacrylate oligomer, a trimethacrylate oligomer, a diacrylate oligomer, or a dimethacrylate oligomer of tris(2-hydroxyethyl)isocyanurate; a triacrylate oligomer, a trimethacrylate oligomer, a diarylate oligomer, or a dimethacrylate oligomer of di(2-hydroxyethyl)mono(2-hydroxyheptane)isocyanurate; and a compound (molecular weight of 1,200 or more) containing (meth)acryloyloxy groups at both ends connected by a urethane bond. The polyfunctional urethane (meth)acrylate oligomer may be a commercially available product. Specific examples of commercially available products include, but are not limited to, UN-3320HC (Negami Electric Industries), UA-510H (Kyoeisha Chemical), CN968 (Sartomer), Eb-220 (Daicel Cytec), and U6HA (Shin-Nakamura Chemical). In the present invention, a hexafunctional urethane acrylate oligomer may be preferably used.
[0188] The hard coat layer may contain one or more types of (meth)acrylate oligomers as the component (A).
[0189] <Component (B)> [(Meth)acrylate monomer] The (meth)acrylate monomer, which is the component (B) used in the present invention, is one in which a (meth)acryloyl group exists as a functional group in the molecule, and includes monofunctional monomers and bifunctional monomers. The upper limit of the molecular weight of the monomer is less than 200, preferably 190 or less, and more preferably 180 or less. If the molecular weight of the monomer is 200 or more, the adhesion to the high-hardness resin layer may be significantly reduced. The lower limit of the molecular weight of the monomer is about 100. The viscosity of the monomer at 25° C. is preferably 15 cps or less, more preferably 10 cps or less, even more preferably 7 cps or less, and particularly preferably 5 cps or less. The viscosity of the monomer can be measured at 25° C. using a vibration viscometer VM-100A-L manufactured by Sekonic.
[0190] Examples of monofunctional monomers having a molecular weight of less than 200 include (meth)acrylic acid and (meth)acrylic acid esters. Specific examples of (meth)acrylate monomers include ethyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-(allyloxymethyl)methyl acrylate, diethylene glycol monoethyl ether acrylate, and acrylic acid=3,3,5-trimethylcyclohexyl acrylate.
[0191] Specific examples of difunctional (meth)acrylate monomers having a molecular weight of less than 200 include 1,4-butanediol diacrylate and ethylene glycol di(meth)acrylate.
[0192] The hard coat layer may contain one or more types of (meth)acrylate monomers as the component (B).
[0193] <Component (C)> [Photopolymerization initiator] The photopolymerization initiator may be a monofunctional photopolymerization initiator.Specific examples include 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone [Darocure 2959: manufactured by Merck]; α-hydroxy-α,α'-dimethylacetophenone [Darocure 1173: manufactured by Merck]; acetophenone-based initiators such as methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone [Irgacure-651: manufactured by BASF], and 1-hydroxy-cyclohexylphenylketone [Irgacure 184: manufactured by BASF]; benzoin ether-based initiators such as benzoin ethyl ether and benzoin isopropyl ether; and other halogenated ketones, acylphosphinoxides, and acylphosphonates.
[0194] <Component (D)> [Surface modifier] The surface modifier is an agent that changes the surface performance of the hard coat layer, such as a leveling agent, an antistatic agent, a surfactant, a water- and oil-repellent agent, inorganic particles, or organic particles.
[0195] Examples of the leveling agent include polyether-modified polyalkylsiloxane, polyether-modified siloxane, polyester-modified hydroxyl-containing polyalkylsiloxane, polyether-modified polydimethylsiloxane having an alkyl group, modified polyether, and silicon-modified acrylic.
[0196] Examples of the antistatic agent include glycerin fatty acid ester monoglycerides, glycerin fatty acid ester organic acid monoglycerides, polyglycerin fatty acid esters, sorbitan fatty acid esters, cationic surfactants, and anionic surfactants.
[0197] Examples of the surfactant and the water / oil repellent agent include fluorine-containing surfactants and water / oil repellents such as an oligomer containing a fluorine-containing group and a lipophilic group, and an oligomer containing a fluorine-containing group, a hydrophilic group, a lipophilic group, and a UV-reactive group.
[0198] Examples of the inorganic particles include silica particles, alumina particles, zirconia particles, and glass particles.
[0199] Examples of the organic particles include acrylic particles and silicon particles.
[0200] The hardcoat layer may contain one or more surface modifiers.
[0201] [Method of forming hard coat layer] The method for forming the hard coat layer is not particularly limited. For example, the hard coat layer can be formed by applying a hard coating composition onto a layer (high-hardness resin layer) located below the hard coat layer, and then photopolymerizing the composition.
[0202] The method for applying the hard coating composition (polymerizable composition) is not particularly limited, and any known method can be used, such as spin coating, dipping, spraying, slide coating, bar coating, roll coating, gravure coating, meniscus coating, flexographic printing, screen printing, beat coating, and brushing.
[0203] The lamp used for light irradiation in photopolymerization has an emission distribution of 420 nm or less. Examples of such lamps include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps. Among these, high pressure mercury lamps or metal halide lamps are preferred because they efficiently emit light in the active wavelength range of the initiator and do not emit a lot of short wavelength light that reduces the viscoelastic properties of the resulting polymer due to crosslinking, or long wavelength light that heats and evaporates the reaction composition.
[0204] The irradiation intensity of the lamp is a factor that determines the degree of polymerization of the resulting polymer, and is appropriately controlled for each performance of the target product. When a typical cleavage-type initiator having an acetophenone group is blended, the illuminance is 0.1 to 300 mW / cm 2 In particular, a metal halide lamp is used, and the illuminance is set to 10 to 40 mW / cm. 2 It is preferable to set the above.
[0205] The photopolymerization reaction is inhibited by oxygen in the air or oxygen dissolved in the hard coating composition. Therefore, it is desirable to carry out the light irradiation using a method that can eliminate the reaction inhibition caused by oxygen. One such method is a method in which the hard coating composition is covered with a film made of polyethylene terephthalate or Teflon to prevent contact with oxygen, and light is irradiated to the hard coating composition through the film. In addition, the composition may be irradiated with light through a light-transmitting window in an inert atmosphere in which oxygen is replaced with an inert gas such as nitrogen gas or carbon dioxide gas.
[0206] When the light irradiation is performed under an inert atmosphere, a certain amount of inert gas is always introduced to keep the oxygen concentration of the atmosphere at a low level. The introduction of the inert gas generates an airflow on the surface of the hard coating composition, causing monomer evaporation. In order to suppress the level of monomer evaporation, the airflow speed of the inert gas is preferably 1 m / sec or less, more preferably 0.1 m / sec or less, as a relative speed to the laminate coated with the hard coating liquid moving under the inert gas atmosphere. By setting the airflow speed within the above range, monomer evaporation due to the airflow is substantially suppressed.
[0207] In order to improve the adhesion of the hard coat layer, the coated surface may be pretreated by known methods such as sandblasting, solvent treatment, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet treatment, and primer treatment using a resin composition.
[0208] The hard coat layer may be further modified. For example, one or more of anti-glare treatment, anti-reflection treatment, antifouling treatment, antistatic treatment, weather resistance treatment, and anti-glare treatment may be applied. The method of these treatments is not particularly limited, and known methods may be used. For example, a method of applying a reflection reducing paint, a method of depositing a dielectric thin film, a method of applying an antistatic paint, etc. may be mentioned.
[0209] The anti-glare treatment is not particularly limited, but may be a method using an anti-glare mold. For example, a high-hardness resin layer, a coating film obtained by applying a hard coating composition, and an anti-glare mold are laminated in this order. Then, the hard coating composition is photopolymerized, and the anti-glare mold is demolded. The photopolymer (hard coat layer) of the hard coating composition has a shape that reflects the rough surface of the anti-glare mold at the contact surface with the anti-glare mold. The material of the anti-glare mold is not particularly limited as long as it transmits UV light, and glass, transparent resin, etc. are used. Other methods of anti-glare treatment include a method of adding particles to a hard coating composition, a method of treating the surface of the obtained hard coat layer, etc. The haze of the hard coat layer can be adjusted by controlling the type of anti-glare mold used (surface haze, thickness, etc.), the amount of particles added, etc.
[0210] <Laminated resin sheet for molding> The pencil hardness of the laminated resin sheet for molding is preferably 2H or more, more preferably 2H to 4H, and even more preferably 3H to 4H. Since a pencil hardness of 5H or more causes cracks after thermoforming, a pencil hardness of 2H to 4H can achieve both moldability and hardness. The pencil hardness of the laminated resin sheet for molding means the hardness of the hardest pencil that does not leave a scratch when a pencil of gradually increasing hardness is pressed against the surface of the hard coat layer at an angle of 45 degrees and a load of 750 g (pencil scratch hardness test in accordance with JIS K 5600-5-4:1999).
[0211] <Molded products> According to one embodiment of the present invention, there is provided a molded article molded using the above-mentioned moldable laminate resin sheet.
[0212] The molding method is not particularly limited, but thermoforming is suitable due to the characteristics of the laminated resin sheet for molding. Thermoforming can be performed by a method commonly used in the field. Specific thermoforming methods include, for example, heat press molding, compressed air molding, vacuum molding, and TOM molding.
[0213] The molding temperature is preferably 100 to 200°C. EXAMPLES
[0214] Examples of the present invention will be described below, but the present invention is not limited to the embodiments of the examples.
[0215] For the purposes of the examples, the following materials were used as high hardness resins, but the materials are not limited to these.
[0216] High-hardness resin (B4): Nippon Shokubai Polyimilex (registered trademark) PML203 (glass transition temperature: 135°C, melt flow rate at 230°C and 3.8 kg load: 1.6 g / 10 min, refractive index 1.54)
[0217] The following materials were used as components constituting the hard coating composition, and were used in the compounding ratios (parts by mass) shown in Table 1 below. 7600B (Component (A)): Mitsubishi Chemical, 6-functional urethane acrylate oligomer UA-306i (Component (A)): Kyoeisha Chemical Co., Ltd., 6-functional urethane acrylate oligomer CN9006 (Component (A)): Sartomer, 6-functional urethane acrylate oligomer AOMA (component (B)): Nippon Shokubai, 2-(allyloxymethyl)methyl acrylate (monofunctional) (molecular weight: 156, viscosity at 25°C: 2 cps) [ka] THF-A (component (B)): Kyoeisha Chemical Co., Ltd., tetrahydrofurfuryl acrylate (monofunctional) (molecular weight: 156, viscosity at 25°C: 3 cps) [ka] 4EG-A (component that does not meet the requirements of component (B)): Kyoeisha Chemical Co., Ltd., PEG200# diacrylate (bifunctional) (molecular weight: 302, viscosity at 25°C: 10 cps) [ka] IB-XA (component that does not meet the requirements of component (B)): Kyoeisha Chemical, isobornyl acrylate (monofunctional) (molecular weight: 222, viscosity at 25°C: 6 cps) [ka] Irgacure 184 (Component (C)): BASF Ltd., 1-hydroxycyclohexyl phenyl ketone RS-90 (component (D)): Manufactured by DIC Corporation, oligomer containing fluorine-containing groups, hydrophilic groups, lipophilic groups, and UV-reactive groups.
[0218] <Measurement of adhesion of laminated resin sheet for molding (hard coat layer)> In accordance with JIS-K5400-5-6, 25 squares were cut with a cutter blade, six lines vertically and six lines horizontally at 1 mm pitch. Nichiban cellophane tape was firmly attached to the squares and peeled off at an angle of 60 degrees toward the user. If the coating did not peel off, it was considered a pass (○), and if even one square peeled off, it was considered a fail (×).
[0219] <Measurement of Scratch Resistance of Laminated Resin Sheet for Molding (Hard Coat Layer)> Scratch resistance: 100g / cm using #0000 steel wool 2 The test piece was subjected to 15 strokes with a load of 0.01 mm and the test piece was rated as passing (◯) if it had less than five scratches, and as failing (×) if it had five or more scratches.
[0220] <Measurement of pencil hardness of laminated resin sheet for molding (hard coat layer)> The moldable laminated resin sheets produced in the examples and comparative examples were evaluated by a pencil scratch hardness test conforming to JIS K 5600-5-4:1999. Pencils of gradually increasing hardness were pressed against the surface of the hard coat layer at an angle of 45 degrees and a load of 750 g, and the hardness of the hardest pencil that did not leave a scratch was evaluated as the pencil hardness. A hardness of 2H or more was evaluated as pass (○), and a hardness of less than 2H was evaluated as fail (×).
[0221] <Measurement of indentation test (indentation creep, maximum indentation depth) of laminated resin sheet for molding (hard coat layer)> The indentation creep and maximum indentation depth of the hard coat layer were measured using a Fischer HM2000LT under the following measurement conditions: Maximum load: 3mN Hold time when maximum load is reached: 5 seconds Loading speed, unloading speed: 10mN / sec
[0222] <Evaluation of the presence or absence of cracks in the hard coat layer (formability)> The laminated resin sheets for molding produced in the examples and comparative examples were thermoformed, and the presence or absence of cracks in the 50 mmR portion was checked. Those in which no cracks were visually observed were evaluated as pass (◯), and those in which cracks were observed were evaluated as fail (×).
[0223] <Example 1> [Manufacturing pellets of high hardness resin (B4)] 500 ppm of phosphorus additive PEP-36 (ADEKA Corporation) and 0.2 mass% of stearic acid monoglyceride (product name: H-100, Riken Vitamin Co., Ltd.) were added to Polyimilex PML203 (Nippon Shokubai Co., Ltd.), mixed in a blender for 20 minutes, and then melt-kneaded at a cylinder temperature of 240°C using a twin-screw extruder (Toshiba Machine Co., Ltd., TEM-26SS, L / D ≒ 40) with a screw diameter of 26 mm and a polymer filter with a mesh size of 10 μm, extruded into strands, and pelletized with a pelletizer. Pellets of high hardness resin (B4) were produced stably. The pellets of the high hardness resin (B4) had an appearance of ◯ (transparent), a glass transition temperature of 135°C, a melt flow rate of 1.6g / 10min under a load of 3.8kg at 230°C, and a refractive index of 1.54.
[0224] (Manufacture of laminated resin sheets for molding) A laminate consisting of a base material layer and a high-hardness resin layer was molded using a multi-layer extrusion device having a single-screw extruder with a shaft diameter of 35 mm, a single-screw extruder with a shaft diameter of 65 mm, a feed block connected to each extruder, and a T-die connected to the feed block.
[0225] Specifically, the pelletized high-hardness resin (B4) obtained above was continuously introduced into a single-screw extruder with a shaft diameter of 35 mm, and extruded under the conditions of a cylinder temperature of 230° C. and a discharge rate of 2.6 kg / h. Also, a polycarbonate resin (Iupilon E-2000; manufactured by Mitsubishi Gas Chemical, Tg: 149° C., weight average molecular weight (Mw): 34,200) was continuously introduced into a single-screw extruder with a shaft diameter of 65 mm, and extruded under the conditions of a cylinder temperature of 240° C. and a discharge rate of 50.0 kg / h.
[0226] The extruded high-hardness resin and polycarbonate resin were introduced into a feed block equipped with two-type, two-layer distribution pins, and the high-hardness resin and polycarbonate resin were laminated at a temperature of 240 ° C. The sheet was then extruded into a T-die at a temperature of 240 ° C., and cooled while transferring a mirror surface with three mirror-finished rolls at temperatures of 120 ° C., 130 ° C., and 190 ° C. from the upstream side, to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The thickness of the obtained laminate was 2.0 mm, and the thickness of the high-hardness resin layer was 60 μm near the center.
[0227] Using each hard coating composition prepared according to the composition (parts by mass) in Table 1 below, a cured coating film (hard coat layer) was formed on the high-hardness resin layer of the laminate obtained above in the following manner, to obtain each molding laminate resin sheet. The viscosity of each hard coating composition prepared according to the composition (parts by mass) in Table 1 below was measured at 25°C using a Sekonic VM-100A-L vibration viscometer, and the values shown below were obtained. Example 1: 50 cps, Example 2: 65 cps, Example 3: 40 cps, Example 4: 70 cps, Comparative Example 1: 146 cps, Comparative Example 2: 52 cps, Comparative Example 3: 54 cps, Comparative Example 4: 200 cps, Comparative Example 5: 210 cps. The hard coating composition was placed on the high-hardness resin layer side of a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer) heated in a hot air circulation dryer set at 100°C, and drawn with a bar coater so that the coating thickness after curing would be 5 to 10 μm. A 100 μm-thick PET film was placed on top of it and leveled with a hand roller. This was irradiated with ultraviolet light using a metal halide lamp with an output density of 120 W / cm at a position 14 cm below the light source at a conveyor speed of 1.0 m / min to form a cured coating film (hard coat layer). After curing, the PET film was peeled off to obtain a moldable laminated resin sheet having a cured coating film of the hard coating composition.
[0228] (Production of Molded Body) The laminated resin sheet for molding produced above was hot-pressed to produce a molded body. The hot-press machine used was a type that was driven by a servo motor to clamp the mold, and the maximum clamping force was set to 3000 kgf. The produced laminated resin sheet for molding was placed in a tray dryer set at 120°C and preheated for 3 minutes. The temperature of the sheet when taken out of the tray dryer was 80°C. After removing the laminated resin sheet for molding from the shelf dryer, it was placed on the lower die of an aluminum hot press die (Fig. 1) within 50 seconds. The laminated resin sheet for molding was hot-press molded in an aluminum hot-press mold (Fig. 1) with a clearance (the gap between the top and bottom of the mold to sandwich the sheet for molding) of 2 mm and a lower mold with a curvature radius R of 50 mm. The temperature of both the top and bottom molds was 138°C, the mold clamping force was 200 kgf, and the pressing time was 3 minutes.
[0229] The evaluation results of the obtained molding laminate resin sheets are shown in the following Table 1. The molding laminate resin sheets of Examples 1 to 4 satisfied all the performances. On the other hand, the molding laminate resin sheets of Comparative Examples 1 to 5 did not satisfy all the performances, and were overall judged to be unsatisfactory.
[0230] [Table 1]
[0231] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.
Claims
1. a high-hardness resin layer containing a high-hardness resin; a substrate layer including a polycarbonate resin (a1) disposed on one surface side of the high-hardness resin layer; A hard coat layer disposed on the other surface side of the high-hardness resin layer, the hard coat layer has an indentation creep of 7.0% or less and a maximum indentation depth of 890 nm or less in an indentation test; The hard coat layer is (A) a 2- to 15-functional (meth)acrylate oligomer, (B) a mono- or di-functional (meth)acrylate monomer having a molecular weight of less than 200; (C) a photopolymerization initiator, and (D) Surface Modifier A hard coating composition comprising the content of the component (C) is 1.2 to 1.8 parts by mass per 100 parts by mass of the total of the components (A), (B), (C), and (D),
2. 2. The molding laminate resin sheet according to claim 1, wherein the indentation creep in the indentation test is 5.3 to 7.0%, and the maximum indentation depth is 700 to 890 nm.
3. the content of the component (A) is 40 to 70 parts by mass per 100 parts by mass of the total of the components (A), (B), (C), and (D), the content of the (B) component is 20 to 55 parts by mass per 100 parts by mass of the total of the (A), (B), (C), and (D) components, The content of the (D) component is 0.1 to 10 parts by mass per 100 parts by mass of the total of the (A), (B), (C), and (D) components. The moldable laminate resin sheet according to claim 1 or 2.
4. The molding laminated resin sheet according to any one of claims 1 to 3, wherein the polycarbonate resin (a1) is an aromatic polycarbonate resin.
5. The aromatic polycarbonate resin is represented by the following formula (3a): 【Chemistry 1】 The molding laminate resin sheet according to any one of claims 1 to 4, comprising a structural unit represented by:
6. The molding laminate resin sheet according to any one of claims 1 to 5, wherein the content of the polycarbonate resin (a1) is 75 to 100 mass% based on the total mass of the base layer.
7. 7. The molding laminate resin sheet according to claim 1, wherein the content of the high hardness resin is 70 to 100% by mass based on the total mass of the high hardness resin layer.
8. 8. The moldable laminate resin sheet according to claim 1, wherein a total thickness of the base layer and the high-hardness resin layer is 0.5 to 3.5 mm.
9. The molding laminate resin sheet according to any one of claims 1 to 8, wherein the ratio of the thickness of the base material layer to the total thickness of the base material layer and the high-hardness resin layer is 75% to 99%.
10. The moldable laminated resin sheet according to any one of claims 1 to 9, wherein the pencil hardness of the surface of the hard coat layer is 2H or more.
11. A molded article molded using the moldable laminate resin sheet according to any one of claims 1 to 10.
Citation Information
Patent Citations
Curved member production method and hard-coated polycarbonate resin layered body for heat bending
WO2021070632A1